2008
DOI: 10.1074/jbc.m710492200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Extracellular Signal-regulated Kinase 1/2 and p38 MAPK as Regulators of Human Sperm Motility and Acrosome Reaction and as Predictors of Poor Spermatozoan Quality

Abstract: Mature spermatozoa acquire progressive motility only after ejaculation. Their journey in the female reproductive tract also includes suppression of progressive motility, reactivation, capacitation, and hyperactivation of motility (whiplash), the mechanisms of which are obscure. MAPKs are key regulatory enzymes in cell signaling, participating in diverse cellular functions such as growth, differentiation, stress, and apoptosis. Here we report that ERK1/2 and p38 MAPK are primarily localized to the tail of matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(135 citation statements)
references
References 56 publications
5
128
1
1
Order By: Relevance
“…Almog et al (37) found prominent ERK1/2 immunoreactivity in the human sperm flagellum and showed that stimulation with OAG promoted phosphorylation of ERK1/2 and produced modest increases in motility. De Lamirande and Gagnon (38) also found that a transient rise in ERK1/2 activity during capacitating incubations of human sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Almog et al (37) found prominent ERK1/2 immunoreactivity in the human sperm flagellum and showed that stimulation with OAG promoted phosphorylation of ERK1/2 and produced modest increases in motility. De Lamirande and Gagnon (38) also found that a transient rise in ERK1/2 activity during capacitating incubations of human sperm.…”
Section: Discussionmentioning
confidence: 99%
“…by Hofmann (2004)). In spermatozoa, PKC was found to participate in sperm capacitation, acrosome reaction, and motility (Breitbart et al 1992, Breitbart & Naor 1999, Cohen et al 2004, Almog et al 2008.…”
Section: Cmentioning
confidence: 99%
“…In an in vivo study in rats, Jia et al (2009) showed that MAPK14 is the key signalling pathway involved in heat-induced testicular germ cell apoptosis, inducing Bcl2 phosphorylation, which leads to its inactivation and subsequent activation of the mitochondria-dependent death pathway, mainly as a result of an imbalance in the Bax : Bcl2 ratio. Importantly, the key components of the MAPK signalling pathway, such as extracellular signal-regulated kinase (ERK) and MAPK kinase (MEK), have also been identified within human ejaculated spermatozoa (de Lamirande and Gagnon 2002;O'Flaherty et al 2005;Almog et al 2008;Du Plessis et al 2010). …”
Section: Introductionmentioning
confidence: 99%